Development of an antioxidant formula based on peanut by‐products and effects on sensory properties and aroma stability of fortified peanut snacks during storage. (11th August 2020) - Albergamo, Ambrogina; Salvo, Andrea; Carabetta, Sonia; Arrigo, Sara; Di Sanzo, Rosa; Costa, Rosaria; Dugo, Giacomo; Russo, Mariateresa
Abstract: BACKGROUND: An antioxidant formula based on peanut skins and hulls was developed and characterized for total and single polyphenols, as well as antioxidant power, considering the contribution provided by each peanut by‐product. Subsequently, it was evaluated for its effect on the sensory properties and aroma stability of peanut bars over a 100‐day period. To this purpose, snacks fortified, or not, with the natural additive were experimentally produced. RESULTS: Peanut hulls contributed to a greater extent than skins with respect to boosting the content of bioactives and the antioxidnt activity of the antioxidant formula, which was marked by a phenol content of (approximately 807 mg gallic acid equivalents g −1 ) and a 2, 2‐diphenyl‐1‐picrylhydrazyl activity similar to that of butylated hydroxytoluene (85.96% and 89.30%, respectively). From a sensory perspective, the incorporation of the formulation in snacks caused only a slightly stronger perception of astringent and bitter notes. Pyrazines, phenol, furan and pyrrole derivatives defined the aroma of snacks, being more abundant in fortified than in conventional samples. Such volatiles faded over storage, with different trends in the examined products. For example, the sum of 2, 5‐dimethylpyrazine, 2‐ethylpyrazine and 2, 3‐dimethylpyrazine was 9.49 and 8.87 ppm at day 15; 5.57 and 7.16 ppm at day 45; and 5.03 and 4.65 ppm at day 100, respectively, in fortified and conventional snacks. Hydroxymethylfurfural decreased constantly over storage in conventional samples and only after day 45 in fortified bars. CONCLUSION: Overall, the antioxidant formulation did not compromise the sensory desirability of peanut snacks and induced a preservative effect on their aroma, especially during the first 15 days of storage. © 2020 Society of Chemical Industry